A SEMANTIC ANALYSIS OF METAPHORS OF BETRAYAL AND EMOTIONALITY IN SERIES ‘LAYANGAN PUTUS’ - Monika Sinaga; Bernieke Anggita Ristia Damanik (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The web series Layangan Putus, produced by MD Entertainment and directed by Benni Setiawan, premiered in November 2021 on WeTV and iFlix. This study examines metaphors related to betrayal and emotional expression in the series from a semantic perspective. It focuses on how emotional and psychological conflicts are conveyed through metaphorical language, especially those that reflect themes of infidelity, heartbreak, and inner turmoil. The research utilizes a qualitative descriptive method with a semantic analysis approach, analyzing dialogues and scenes using Lakoff and Johnson's Conceptual Metaphor Theory, as outlined in Metaphors We Live By. According to this theory, metaphors are fundamental to how we understand abstract concepts, comparing them to more concrete experiences like money, journeys, or warfare. The study finds that metaphors of betrayal often stem from domains such as war, destruction, and fragmentation (e.g., “inner war,” “shattered into pieces”), while emotional metaphors often draw from physical sensations and natural elements (e.g., “explosive,” “like a storm”). These metaphors enhance the narrative and deepen the audience's emotional connection with the characters. Ultimately, metaphor in Layangan Putus serves as a key element in shaping the story’s emotional impact and audience engagement.